Strategies of Translating Euphemistic Expressions from Arabic into English: A Comparative Study of Artificial Intelligence Models with Human Translation - Baleigh Qassim Al-Wasy; Othman Saleh Mahdy Mohammed (Taez University, 2024)
Euphemism is used to soften rude expressions or words. Translating euphemisms is a very challenging task for human translators and will be more difficult for AI applications. Almost all previous studies have clustered around studying the efficiency, accuracy, coherence and cohesion of AI translation in comparison to human translation. However, these studies have not tackled the strategies used in both types of translations. Consequently, this study aims to identify the strategies utilized by AI Models with human translation when translating euphemistic expressions from Arabic into English. Additionally, it aims to evaluate how these methods influence the translation accuracy of both human translators and AI models in both directions of translation (Arabic to English and English to Arabic). The researchers have utilized some euphemistic expressions taken from the Holy Quran, Prophetic Hadiths, and some previous studies. These expressions have been inputted into AI models. The outcomes of these AI models are compared to Human translation, using Baker's (2013) translation strategies. Researchers have analysed the collected data quantitatively. The results revealed that translation by a more general word and translation by cultural substitution strategies were mostly used by human translation whereas translation using a loan word strategy is mostly used by AI models. The findings also showed that human translators outperform AI models regarding cultural substitution. It has been found that the direction of language plays a crucial role in AI outcomes, as they perform better when translating from English into Arabic.